Optimal CEO Compensation: Some Equivalence Results - Choe, Chongwoo (Journal of Labor Economics, 2006)
I study optimal managerial contracts in two contracting environments. When the investment return is contractible, an optimal contract combines a base salary, golden parachute, and bonus. When the return is not contractible, two types of optimal contracts are studied: a contract with restricted stock and a contract with stock options. These three types of contracts are equivalent: they implement the same outcome and lead to the same expected payoff for the manager, implying that the choice of contractual form is irrelevant in the environment I study. I suggest directions of research for the relevance of different contractual forms.